ANALYSIS OF HISTORICAL INFORMATION AND INDIGENOUS KNOWLEDGE OF THE BLAMBANGAN KINGDOM IN THE OMAHSEUM MUSEUM COLLECTIONS: Analisis Informasi Sejarah dan Pengetahuan Lokal Kerajaan Blambangan dalam Koleksi Museum Omahseum - Rizki Nurislaminingsih; Heriyanto; Wiwin Indiarti; Fitri Perdana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Banyuwangi is increasingly prominent with its annual cultural performances. A variety of cultural products are presented to the public, including rituals, dance, music, and literature. All these are believed to be the legacy of the Blambangan Kingdom. Museums can play a role in Banyuwangi's efforts to demonstrate its identity to the public by exploring the background of the community's ancestral kingdom, the Blambangan Kingdom. This also underlies the purpose of this research, which is to analyze information about the history and indigenous knowledge of the Blambangan Kingdom community in the collections at the Omahseum Museum. This museum houses artifacts left behind by the kingdom. We used qualitative research with a museum studies approach. Data collection was conducted through observation, interviews, collection analysis, text analysis, and documentation of artifacts. The results show that the Omahseum Museum collections contain historical information and holds narrative evidence of the formation of Blambangan into Banyuwangi. The collections also contain information about local knowledge about the creation of writing media from palm leaves, natural ink, literary arts, clay processing, and metallurgy. The conclusion of this research is that the collection at the Omahseum Museum contains historical information (locations, name of Banyuwangi, and war) and indigenous knowledge (written media, literary arts, clay processing, and metal processing). The collection has the potential to become a source of local history teaching and museum interpretations based on local knowledge. The results of this study can inspire museum managers to expand their information services on the local knowledge behind each collection.